Gender Differences in Criminal Recidivism - Sulejmanović, Dijana (NBP. Nauka, bezbednosti, policija, 2024)
Gender plays a crucial role in shaping the dynamics of criminal behavior and its recurrence within society. While the study of recidivism often focuses on general trends and risk factors, understanding how gender influences these patterns provides deeper insights into prevention and rehabilitation strategies. This article examines gender differences in criminal behavior and recidivism through a comprehensive review of existing literature, empirical analyses of recidivism data, and qualitative insights from stakeholders within the criminal justice system. It also provides a review of relevant literature, synthesizing theoretical perspectives and empirical findings on gender differences in criminal behavior. Understanding the pathways to recidivism requires considering the unique challenges faced by male and female offenders upon release from incarceration or supervision. For men, recidivism often stems from factors such as peer influence, substance abuse, and difficulties in finding stable employment, while women are more likely to experience recidivism due to issues such as trauma-related disorders, a lack of social support, and limited access to resources for mental health treatment or housing. Moreover, the reintegration process for female offenders is complicated by responsibilities such as childcare and family reunification, which can influence their likelihood of reoffending. These gender-specific pathways highlight the need for tailored intervention programs that address the underlying causes of criminal behavior and recidivism and provide support systems conducive to successful reintegration into society.